2018
DOI: 10.1007/s40095-018-0291-7
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and sensitivity analyses applied to a dynamic simulation of the carbon dioxide concentration in a detached house

Abstract: This paper aims to study the variability of indoor CO 2 concentration due to occupant behaviour and physical parameter uncertainties. A case study, conducted in a mechanically ventilated detached house, is presented with an uncertainty and sensitivity analysis (Monte Carlo method with a Latin hypercube sampling). Uncertainties related to occupant behaviour are described by combining four types of scenarios: occupation, generation of CO 2 per person, indoor doors, and outdoor windows' openings. The uncertainty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…In our study, the average concentration during the night was similar in both bedrooms, at 1077 ppm (teenager) and 1103 ppm (child), which is comparable with the average CO 2 concentration in unoccupied bedrooms (999 ppm and 1236 ppm in South and North bedrooms, respectively) as reported by Bouvier et al [25]. In occupied bedrooms, the authors in [25] reported higher (1585 ppm and 1760 ppm in South and North bedrooms, respectively) than our average concentration of CO 2 , which was 766 ppm and 860 ppm with open doors and 1402 ppm and 1337 ppm with closed doors, in the teenager's and the child's bedroom, respectively (Figure 3). However, it is similar to the average CO 2 concentration of 716 ppm measured in 13 bedrooms located in Athens' residences [39].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our study, the average concentration during the night was similar in both bedrooms, at 1077 ppm (teenager) and 1103 ppm (child), which is comparable with the average CO 2 concentration in unoccupied bedrooms (999 ppm and 1236 ppm in South and North bedrooms, respectively) as reported by Bouvier et al [25]. In occupied bedrooms, the authors in [25] reported higher (1585 ppm and 1760 ppm in South and North bedrooms, respectively) than our average concentration of CO 2 , which was 766 ppm and 860 ppm with open doors and 1402 ppm and 1337 ppm with closed doors, in the teenager's and the child's bedroom, respectively (Figure 3). However, it is similar to the average CO 2 concentration of 716 ppm measured in 13 bedrooms located in Athens' residences [39].…”
Section: Discussionsupporting
confidence: 91%
“…When an individual does not get enough sleep to feel awake and alert, they begin to experience symptoms of sleep deprivation such as yawning, irritability, fatigue, inability to concentrate, moodiness, forgetfulness, lack of motivation, depression, and poor perspective on life [3]. In our study, the average concentration during the night was similar in both bedrooms, at 1077 ppm (teenager) and 1103 ppm (child), which is comparable with the average CO 2 concentration in unoccupied bedrooms (999 ppm and 1236 ppm in South and North bedrooms, respectively) as reported by Bouvier et al [25]. In occupied bedrooms, the authors in [25] reported higher (1585 ppm and 1760 ppm in South and North bedrooms, respectively) than our average concentration of CO 2 , which was 766 ppm and 860 ppm with open doors and 1402 ppm and 1337 ppm with closed doors, in the teenager's and the child's bedroom, respectively (Figure 3).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations